PENGARUH DIGITAL MARKETING, PERCEIVED QUALITY DAN PERSONAL SELLING TERHADAP PENJUALAN PRODUK TAHU (STUDI KASUS : PENGRAJIN TAHU DI KEDIRI) - Puji Astutik; Daniel Daniel; Sony Fridayanto; Herman Kusbandono (Jurnal Riset Entrepreneurship, 2021)
During the pandemic, tofu craftsmen in Kediri complain about the turnover and the reduction in workforce. This requires a step to determine the role of digital marketing, perceived quality, and personal selling on selling these tofu products and measuring this research's part. This study used 60 respondents, namely tofu craftsmen, to be given a questionnaire. They were taking respondents using probability sampling techniques. This research method uses linear regression statistical analysis techniques. They are starting with the validity test, reliability test, classical assumption test, multiple linear regression test, partial test, simultaneous test, and determination coefficient. This study's results are digital marketing has no effect on product sales partially, while perceived quality and personal selling have an impact on product sales partially. Meanwhile, simultaneously all independent variables simultaneously influence the dependent variable. The success rate of this study was 64.8%. This research can be increased again, the role of the variables to have a high level of influence by filling out the questionnaire in an educational manner according to the conditions of observation that have been made.